Deteksi Endoparasit Cacing pada Hepar Tikus Laboratorium (Rattus norvegicus) dari Sentra Peternak di Kabupaten Banyumas dan Kabupaten Purbalingga - Dita Pratiwi Kusuma Wardani; Kurnia Ritma Dhanti; Arif Mulyanto; Tantri Analisawati Sudarsono (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2021)
The presence of laboratory rats that are maintained and bred for laboratory purposes or laboratory observations is very necessary. The presence of endoparasite in laboratory rats will have an impact on the result of the research or laboratory observations. This study aims to detect helminth endoparasites in the liver of laboratory rats (Rattus norvegicus) from animal breeders in Banyumas and Purbalingga Districts. This research was an observational study with a cross-sectional design. A total of 52 laboratory rats were used in the study. Rats are killed with chloroform, liver surgery then identify the presence of worm larvae. Out of the 52 rats obtained, 7 (29.17%) from 24 laboratory rats in Banyumas District and 5 (17.86%) from 28 laboratory rats in Purbalingga District were infected with Taenia taeniaeformis. It is necessary to control helminth infections in laboratory rats, such as laboratory animal quarantine, health monitoring, and antihelmintic treatment. It is important to handle carefully during travel to assure the results of research or laboratory observations using the animals.